Lysine-based amino-functionalized lipids for gene transfection: 3D phase behaviour and transfection performance12. Issue 25 (18th June 2018) - Tassler, Stephanie; Pawlowska, Dorota; Janich, Christopher; Giselbrecht, Julia; Drescher, Simon; Langner, Andreas; Wölk, Christian; Brezesinski, Gerald
Abstract : New cationic lipids designed for non-viral gene transfection form lamellar and non-lamellar mesophases in aqueous dispersions. The lipid mixtures with DNA show a panoply of mesophases. Surprisingly, the lamellar lipoplex with OO10 has the best transfection performance in different cell lines. Abstract : Based on previous work, the influence of the chain composition on the physical–chemical properties of five new transfection lipids (TH10, TT10, OH10, OT10 and OO10) containing the same lysine-based head group has been investigated in aqueous dispersions. For this purpose, the chain composition has been gradually varied from saturated tetradecyl (T, C14:0 ) and hexadecyl (H, C16:0 ) chains to longer but unsaturated oleyl (O, C18:1 ) chains with double bonds in the cis configuration. In this work, the lipid dispersions have been investigated in the absence and presence of the helper lipid DOPE and calf thymus DNA by small-angle and wide-angle X-ray scattering (SAXS/WAXS) supplemented by differential scanning calorimetry (DSC), attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR) and Fourier-transform Raman spectroscopy (FTRS). Lamellar and inverted hexagonal mesophases have been observed in single-component systems. In the binary mixtures, the aggregation behaviour changes with an increasing amount of DOPE from lamellar to cubic. The lipid mixtures with DNA show a panoply of mesophases. Interestingly, TT10 and OT10 form cubic lipoplexes, whereas OO10 complexes the DNA sandwich-like between lipid bilayers in a lamellar lipoplex. Surprisingly, the latter is the most effective lipoplex.